Indicadores de inmunidad pasiva y activa en neonatos bovinos de madres vacunadas y no vacunadas con una bacterina comercial (2020)
The aim of this study was to evaluate the immune response and passive immunity transfer through serological indicators analyzed by Radial Immunodiffusion (RID) and colostrum quality in the low tropics, after the application of three treatments in cows in the last third of pregnancy with their respective calves. Bacterial vaccines were given in cows before calving and in a group of calves on the first postpartum day. 21 pregnant cows from the low tropic were distributed in three groups, T1: control, T2: application of a dose of commercial bacterial vaccine 30 days before parturition, T3: application of vaccine 30 and 15 days before parturition, plus a T4 (n=7): application of vaccine in calves at 24 hours post birth. The experimental time for cows was 30 days pre-parturition and one day post-parturition, for calves was 24±6 and 72 hours post-birth. The variables allowed to analyze colostrum quality and passive immune transference. In cows the colostrum quality, the TP, albumin, ALT and cortisol did not show statistical differences within treatments, while AST was different at T3. In calves the IgG and IgM did not show statistical differences within treatments nor hours post-birth, the IgM and albumin were statistically different in within treatments, meanwhile globulins and total protein were statistically different at the hours post-birth. There was no failure in passive immune transference.